Isolation and characterization of microsatellite markers in the tetraploid birch, Betula pubescens ssp. tortuosa - Truong, C.; Palmé, A. E.; Felber, François; Naciri-Graven, Y. (My University, 2004)
The mountain birch, Betula pubescens ssp. tortuosa is a tetraploid tree species which forms the tree limit in northern Fennoscandia. We identified nine polymorphic microsatellite loci in order to characterize the genetic structure of populations at different elevations close to the treeline. The microsatellite loci were highly polymorphic, with 14–42 alleles per locus and an average expected heterozygosity of 0.73 ± 0.25 under random chromosome segregation and 0.68 ± 0.23 under random chromatid segregation.
Keywords: autopolyploidy; genetic structure; microsatellite markers; mountain birch; nonradioactive probes